Manajemen Bisnis Aerotropolis (Airport City): Sebuah Studi Pemetaan Sistematis - Jajang Ginanjar; Muhamad Rizal; Ria Arifianti (Program Studi Manajemen Fakultas Ekonomi UMRAH, 2021)
The application of the concept of aerotropolis (airport city) in various parts of the world requires holistic planning. Aspects that affect the implementation of airport cities must be considered in planning. The linkage between regulations, government support, business schemes, land ownership, and human resources, is an important capital in realizing an airport city. This study is an initial research that aims to identify the results of research that has been carried out in the field of Aerotropolis business management using a systematic mapping study (SMS). The purpose of this mapping is to find out what Aerotropolis topics are being researched. This article focuses on 10 airport cities in the world that have applied the Aerotropolis model in their development, namely Amsterdam, Paris, Dubai, Dallas, Chicago, Memphis, Hong Kong, Singapore, Incheon, and Washington. This study uses a qualitative method by going through a literature study. The search is done through Google Scholar. It is intended that the output of this SMS can describe opportunities with the aim of exploring topics and new ideas in managing the Aerotropolis (aerocity-airport city) business apart from exploiting previously existing topics. Recommendation of study results from Aerotropolis Development with a research focus on Aerotropolis Development Practices. Qualitative methods are mostly used in research on this Aerotropolis.